Answer: -4, -3, -2
Step-by-step explanation:
By inspection, we know
is a root.
We can thus rewrite the equation as
![(x+2)\left(\frac{x^3 + 9x^2 + 26x+24}{x+2} \right)=0\\\\(x+2)(x^2 + 7x+12)=0\\\\(x+2)(x+3)(x+4)=0\\\\x=-4, -3, -2](https://tex.z-dn.net/?f=%28x%2B2%29%5Cleft%28%5Cfrac%7Bx%5E3%20%2B%209x%5E2%20%2B%2026x%2B24%7D%7Bx%2B2%7D%20%5Cright%29%3D0%5C%5C%5C%5C%28x%2B2%29%28x%5E2%20%2B%207x%2B12%29%3D0%5C%5C%5C%5C%28x%2B2%29%28x%2B3%29%28x%2B4%29%3D0%5C%5C%5C%5Cx%3D-4%2C%20-3%2C%20-2)
Answer:
A) Neither
Step-by-step explanation:
If two lines have same slope then they are parallel lines
If slope of line1* slope of line 2 = -1
The the two lines are perpendicular
In this question slope of line = 2\7
Slope of line 2 = 7\2
Attendance with the higher ticket price is ...
... $1750/$7 = 250
So the percentage change in attendance is ...
... change = (new - original)/original × 100%
... = (250 -300)/300 × 100% = -1/6×100% ≈ -17%
2abc - 3ab ║ 2 (2) (3) (4) - 3 (2) (3)
You would multiply and the products - you are going to subtract
2 × 2 × 3 × 4 = 48
3 × 2 × 3 = - 18
-------
answer: 30